Reliability and correlation between two physical tests doing specific movements by parakarate athletes - Villacieros-Rodríguez, J.; Roldán-Cruz, A.; Casas-Castellano, E.; Martín-Morell, A. M.; Muñoz-Cutuli, L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Nowadays, it is very common to find athletes with intellectual disability (ID) practicing karate. To assess their physical fitness, it is necessary to use appropriate tools which allow the assessment of their physical capacities taking into account their specific characteristics (Cabeza-Ruiz, 2020). The aim of this work is to study the reliability and correlation of two tests doing specific movements applied to karate for people with intellectual disabilities.